Boundary and Interior Layers, Computational and Asymptotic Methods - BAIL 2014 - Knobloch, Petr.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume offers contributions reflecting a selection of the lectures presented at the international conference BAIL 2014, which was held from 15th to 19th September 2014 at the Charles University in Prague, Czech Republic. These are devoted to the theoretical and/or numerical analysis of problems involving boundary and interior layers and methods for solving these problems numerically. The authors are both mathematicians (pure and applied) and engineers, and bring together a large number of interesting ideas. The wide variety of topics treated in the contributions provides an excellent overview of current research into the theory and numerical solution of problems involving boundary and interior layers.  .
Keywords: Computer mathematics; Partial differential equations; Differential equations; Computational Mathematics and Numerical Analysis; Partial Differential Equations; Ordinary Differential Equations